Recognize Max Weber's Social Action Theory in Individual Social Transformation - Fatah, Rahmat Abd (International Journal of Multidisciplinary Approach Research and Science, 2024)
Every individual in his social reality always performs social actions, whether in a state of realization or not, these actions continue to run dynamically along with the dynamics of self-situation with the reality of his life. This paper uses narrative literature review to recognize Max Weber's Social Action Theory. It is found that Weber's social action theory originated from the formation of a cultural tradition of thought by his father and mother as well as the formal formation of his learning process and was certainly influenced by the German historian, philosopher, economist and political theorist Immanuel Kant (1724-1804) as well as influenced by Nietzsche (1844-1900). It is found that social action always has motives (Intention) and meaning (Meaning) directed to others and to oneself. Transformational social action can be rational which he calls instrumental rationality and value rationality. As well as being Non-Rational. He called it Affection-oriented social action and Traditional Orientation.